Performance Improvement of GeTex-Based Ovonic Threshold Switching Selector by C Doping - Wang, Lun; Cai, Wang; He, Da; Lin, Qi; Wan, Daixing; Tong, Hao; Miao, Xiangshui (IEEE electron device letters, 2021)
In this letter, we fabricated a C-doped GeTe x Ovonic threshold switching (OTS) selector in a via-hole structure. The material composition is simple without toxic element doping. Performance of the GeTe x -based selector is improved to be comparable to commercial GeSe-based selectors through C doping. A selector with advantages of low off-current (2 nA), low threshold voltage (1.26 V) accompanying with a big voltage window (0.55 V), high selectivity ( > 4.2× 10 ^{4} ), satisfactory endurance (> 10 7 cycles with 2 mA on-current), low cycle-to-cycle \text{V}_{{th}} variation and fast operating speed (8.5 ns) was fabricated. Besides, selector with self-limited on-current character was found. Next, reasons behind off-current reduction and consistency improvement by using C doping were studied by First-principles calculations.